Epitaxial growth of icosahedral boron arsenide on silicon carbide substrates: improved process conditions and electrical properties - Zhang, Yi (Kansas State University, 2011)
The exceptional radiation resistance, high melting point, and wide energy bandgap (3.2 eV) of icosahedral boron arsenide, B[subscript]12As[subscript]2, make it an attractive candidate for applications in radiation intense environments, for example, in radioisotope batteries. These devices have potential lifetimes of decades rather than days or weeks that are typical of conventional chemical power cells. Solid state neutron detectors are another potential application of this semiconductor, as the boron-10 isotope has a high thermal neutron capture cross-section, orders of magnitude higher than most elements. To produce high quality crystalline B[subscript]12As[subscript]2 for these applications, this research focused on the epitaxy and electrical properties of B[subscript]12As[subscript]2 thin films. The major findings include the following. Twin-free heteroepitaxial B[subscript]12As[subscript]2 layers were obtained on m-plane 15R-SiC and c-plane 4H-SiC inclined 4° and 7° off-axis in the [1-100] direction. These substrates exposed asymmetric step-terrace surface structures that force B[subscript]12As[subscript]2 layers to adopt a single orientation, thus, twins were eliminated. Consequently, the crystal quality was greatly improved over films on on-axis c-plane 6H-SiC, yielding a maximum hole mobility of 80 cm[superscript]2V[superscript]-1s[superscript]-1, nearly 100 times higher than previously reported values. B[subscript]12As[subscript]2 epilayers grown at 1300°C had the lowest defect densities, smallest residual strains, highest mobility and highest deposition rate. Excess AsH[subscript]3 concentration was advantageous to prevent the loss of arsenic from the epilayer. Undoped B[subscript]12As[subscript]2 exhibited a variable-range-hopping conduction, indicating it was a highly disordered system. All films were p-type with a room temperature hole concentration on the order of 10[superscript]12~10[superscript]15cm[superscript]-3. The thermal activation energy of acceptors varied from 0.15 eV to 0.33 eV. The Hall mobility was dominated by impurity scattering at low temperatures and by polar phonon scattering at high temperatures. H, C, O and Si were the major impurities present in the undoped B[subscript]12As[subscript]2 films with concentrations on the order of 10[superscript]18~10[superscript]19 cm[superscript]-3. Si doping and annealing decreased the resistivity by up to two orders of magnitude. The density of localized states was small in the undoped B[subscript]12As[subscript]2 as the intrinsic acceptor levels (IALs) were compensated by the boron interstitials. However, in Si-doped B[subscript]12As[subscript]2, Si may prevent the interstitial boron atoms from compensating the IALs, yielding a decreased density of localized states. The Hall mobility of B[subscript]12As[subscript]2 epilayer was significantly reduced with increasing silicon concentration.
Keywords: Icosahedral borides; Silicon carbide; Epitaxy; Mobility; Boron arsenide nanowires; Chemical Engineering (0542); Materials Science (0794)